Clinical application of autogenous tooth as bone graft material in extraction socket- A prospective study - Amrita Sah; Shridhar.D. Baliga (Elsevier, 2022)
Introduction: Among the different graft materials used in dental clinics, autogenous bone is the most ideal. However, its biggest short coming is that the amount invested is limited, resorption is unavoidable and a secondary defect is generated at the donor site. Extracted tooth has been discarded as infective medical dust. So, the present study was aimed to evaluate the efficacy of autogenous tooth as graft material in the extraction socket of third molar region. Materials and method: A split mouth study design was undertaken. 20 patients requiring extraction of bilateral mandibular third molars were included in the study. This study was carried out in third molar region. Group A: PRF membrane was placed in the third molar extraction socket. Group B: Autogenous tooth processed into bone graft was used in the third molar extraction socket, over which PRF membrane was placed. Postoperative pain and bone healing were assessed in the post-operative follow-up visits. Results: We observed that Group B showed significantly faster bone healing as compared to Group A, in terms of overall density and trabecular pattern of bone at the end of 3 months and 6 months following extraction. Conclusion: This study clearly indicates that autogenous tooth used as bone graft material showed improved bone healing at the third molar extraction sockets. This study emphasis on use of human dentin as graft material as it was simple, cost effective, required no special armamentarium and infrastructure for preparation and even did not require additional donor site.